2018
DOI: 10.1007/jhep10(2018)178
|View full text |Cite
|
Sign up to set email alerts
|

Leptogenesis via neutrino oscillation magic

Abstract: The possibility of generating the baryon asymmetry of the Universe via flavor oscillation in the early Universe is discussed. After the inflation, leptons are born in some states, travel in the medium, and are eventually projected onto flavor eigenstates due to the scattering via the Yukawa interactions. By using the Lagrangian of the Standard Model with the Majorana neutrino mass terms, llHH, we follow the time evolution of the density matrices of the leptons in this very first stage of the Universe and show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In both cases, if the reheating temperature of the Universe is sufficiently high, the baryon asymmetry can be explained through thermal leptogenesis [37] or through leptogenesis via neutrino oscillation during the thermalization of the Universe [38].…”
Section: Neutrino Scale and Gaugino Massmentioning
confidence: 99%
“…In both cases, if the reheating temperature of the Universe is sufficiently high, the baryon asymmetry can be explained through thermal leptogenesis [37] or through leptogenesis via neutrino oscillation during the thermalization of the Universe [38].…”
Section: Neutrino Scale and Gaugino Massmentioning
confidence: 99%
“…A similar mechanism has been considered in the context of active neutrino oscillation with higher dimensional terms for T R 10 8 GeV [23]. It was shown that baryogenesis is possible in the SM plus the dimension five Majorana neutrino mass term, LLHH, explaining the ordinary neutrino oscillation [24]. The key point is that the leptons, produced from the inflaton decays or the scatterings of the plasma, undergo flavor oscillation due to the thermal masses.…”
Section: Jhep07(2020)174mentioning
confidence: 92%
“…To avoid the proton decays, one can introduce a Z 2 symmetry under which SM leptons are odd but the baryons are even or vise versa. In this case, the baryon asymmetry may be correctly obtained from neutrino oscillation with the higher dimensional term (3.24) [84,85] and also the quark oscillation could be important via the baryon-number-violating but baryon-parity-conserving operator [86]. Lastly, let us mention the confinement of SO(N ).…”
Section: 3 Cosmologymentioning
confidence: 93%